MOTIVASI RELAWAN SOSIAL DALAM PELAKSANAAN BIMBINGAN BELAJAR PLUS DI SEKOLAH RAKYAT KEJAWAN PUTIH SURABAYA - RETNO WAHYUNI; Suhanadji Suhanadji; Gunarti Lestari (Universitas Negeri Surabaya, 2018)
Plus guidance is the activity of providing guidance by social volunteers not only academic learning guidance, but there is moral guidance, religion, giving skills, fostering the culture of reading and recreation. This study aims to describe and analyze the motivation of social volunteers in the implementation of learning guidance plus at Sekolah Rakyat Kejawan Putih Surabaya. This study employed qualitative method. The subjects of this research are School Owners, social volunteers and students. In collecting the data, data collection procedures were using interview, participatory observation, and documentation. The analysis data use five stages including Collecting data, data reduction, rearrangement stage, data presentation stage or data analysis after data collection and conclusion and verification phase. the study applied credibility, dependability, confirmability and transferability. From the results of research conducted by the motivation of social volunteers at Sekolah Rakyat Kejawan Putih Surabaya is responsive to difficult and challenging situations, the desire to accept responsibility, happy to cooperate with others, willingness to help others, empathy to solve other people's problems, to put the experience as a volunteer on the CV when applying for a job, to get new friends, because invited friends who first became volunteers and to fill the spare time. Then the execution of plus learning guidance consisting of academic, religious, moral, skill, academic, religious, moral, skill-raising, reading and recreation guides go well despite inadequate facilities, but it is not the most important social volunteer priority is to make children keep the spirit of learning.